Altered state of consciousness: dance-induced spirit possession and trance (2020)
Spirit possession and trance are very dominant features of Altered State of Consciousness (ASC), especially within religious spheres. However, dance and movement, with the accompaniment of music/sound, create such an enabling environment, for individuals who are so predisposed, to easily and quickly transpose from the normal states of awareness to altered states of mystical interactions. Also critically discussed is the term ASC as both a religious and psychological phenomenon. This paper, therefore, explores ASC within the context of dance, using two different case studies in explaining the intricacies of trance, in particular, and spirit possession.